2010
DOI: 10.1590/s0102-37722010000300012
|View full text |Cite
|
Sign up to set email alerts
|

Developmental levels in adult's conceptions of health and disease

Abstract: -A socio-cognitive developmental perspective suggests that conceptions regarding health and disease processes may present different levels of openness, flexibility, inclusiveness and differentiation, and thus can be ordered into different levels. We present a qualitative study on lay significations regarding health and disease processes, endorsed by 67 adults. The results show that these adults have different socio-cognitive developmental competences related to health and disease processes. For each dimension … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 8 publications
2
3
0
Order By: Relevance
“…However, there were no women with a response typical of the highest level. These findings are not surprising, but are consistent with other empirical studies that found that only a very small number of adults can function at this highest level .…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…However, there were no women with a response typical of the highest level. These findings are not surprising, but are consistent with other empirical studies that found that only a very small number of adults can function at this highest level .…”
Section: Discussionsupporting
confidence: 92%
“…Specifically, results indicate that these women function at varying developmental levels regarding their illness, which are congruent with those of other theoretical and empirical studies in the field of health psychology [22,23,30,31,[47][48][49] and psychotherapy [18,20,25,50]. However, there were no women with a response typical of the highest level.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations